ac-ad+bc-bd
xm-xn+ym-yn
1-b+a-ab
-am-an-bm-bn
6x²-4xy+9xy-6y²=6x²+5xy-6y²
0,25a+1,15a-1,15-5,29
Объяснение:
(a+b)(c-d)=ac-ad+bc-bd
(x+y)(m-n)=xm-xn+ym-yn
(1+a)(1-b)=1-b+a-ab
(a+b)(-m-n)=-am-an-bm-bn
(2x+3y)(3x-2y)=6x^2-4xy+9xy-6y^2=6x^2+5xy-6y^2
(0.5a-2,3)(0.5+2.3)=0,25a+1,15a-1,15-5,29=1,4a-6,44
ac-ad+bc-bd
xm-xn+ym-yn
1-b+a-ab
-am-an-bm-bn
6x²-4xy+9xy-6y²=6x²+5xy-6y²
0,25a+1,15a-1,15-5,29
Объяснение:
(a+b)(c-d)=ac-ad+bc-bd
(x+y)(m-n)=xm-xn+ym-yn
(1+a)(1-b)=1-b+a-ab
(a+b)(-m-n)=-am-an-bm-bn
(2x+3y)(3x-2y)=6x^2-4xy+9xy-6y^2=6x^2+5xy-6y^2
(0.5a-2,3)(0.5+2.3)=0,25a+1,15a-1,15-5,29=1,4a-6,44